Perampasan Ruang Hidup dalam Makna Referensial Alquran - Wahyudi, Chafid; Ahmada, Robbah Munjiddin (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2020)
Deprivation of the living sphere always interconnects with the power, precisely through a scenario of territorial and capitalist interests. In practical terms, deprivation of living space has neglected social aspects, as well as confirmed the occurrence of crisis at the social-ecological level. The crisis can also be categorized as the turbulent relationship between humans and humans with nature. In the Qur’anic referentiality, deprivation of living space is a kind of denial of the mandate of God. The essence of spreading mercy to all, as like giving rights to those who reserve, not doing unjust, no activities that damage and hurt anyone, humans, animals, nature, and all creatures, has been eliminated by the dominance of the sectoral ego. As a result, a form of injustice manifests a series of violence and destruction. As an essential factor in life, it is urgent to return the living space to its position as a social function attached to the material element. In this context, the social capital framework can be a node that could bring the community back to the trusted living, that the living sphere is a common need. The social capital framework will, in turn, bring back the social aspects that are absent from the material elements.